Cardiovascular and Renal Protection in Type 2 Diabetic Hypertensive Patients. The Role of Calcium Channel Blockers (Medical Forum Monthly, 2024)
Objective: To study the effects of Calcium Channel Blocker (Amlodipine) as monotherapy in diagnosed hypertensive, non-insulin dependent diabetes mellitus (NIDDM) patients.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at Jinnah post graduate medical centre (JPMC) Karachi, in collaboration with the department of medicine JPMC, Karachi from July 2010 to January 2011. Materials and Methods: This study is to examine the effects of Amlodipine in type 2 diabetic hypertensive patients with base line proteinuria. 20 normal subjects were also selected as a control group.Results: with CCB (Amlodipine) baseline to final change for SBP as well as DBP was significantly reduced i.e. 24.70 % (p<0.001) and 16.20% (p<0.001) respectively. CCB showed 44% (p<0.001) reduction in FBS, creatinine clearance reduced by 8.10% (p<0.5), serum potassium reduced by 4.50%, non significant increase in serum urea i.e. 3.70% and serum creatinine i.e. 3.8% was observed.Conclusion: Aim of treating hypertension is to control or limit its cardiovascular complications; CCBs are the drug of choice in controlling blood pressure and to prevent the progress of cardiovascular events in patients without diabetic nephropathy as well as reserves for add-on therapy in hypertensive patients complicated with diabetic nephropathy.